Interleukin-35 is upregulated in systemic sclerosis and its serum levels are associated with early disease - Tomcik, Michal; Zerr, Pawel; Palumbo-Zerr, Katrin; Storkanova, Hana; Hulejova, Hana; Spiritovic, Maja; Kodet, Ondrej; Stork, Jiri; Becvar, Radim; Vencovsky, Jiri; Pavelka, Karel; Filkova, Maria; et al. (Rheumatology, 2015)
IL-35 is a member of the IL-12 family consisting of p35/IL-12a and EBI3/IL-27b subunits. IL-35 exerts immunomodulatory activities in experimental and human autoimmune inflammatory conditions. Our aim was to assess IL-35 expression in the skin and circulation of SSc patients and to characterize its potential association with SSc-related features.Expression of IL-35 in skin and dermal fibroblasts was quantified by quantitative PCR, immunohistochemistry and immunofluorescence. Serum levels of IL-35 (by ELISA), CRP (by turbidimetry), ANA (by immunofluorescence) and autoantibodies of the ENA complex (by immunoblot) were measured in 40 SSc patients. Serum IL-35 was determined in 40 age- and sex-matched healthy controls.IL-35 expression was increased in SSc skin and dermal fibroblasts in a TGF-?-dependent manner. IL-35 induced an activated phenotype in resting fibroblasts and enhanced the release of collagen. IL-35 serum levels were increased in patients with SSc compared with healthy controls [median 83.9 (interquartile range 45.1-146.1) vs 36.2 (interquartile range 17.2-49.4) pg/ml, P < 0.0001]. Serum IL-35 was negatively correlated with disease duration (r = -0.4339, P = 0.0052). In line with this finding, serum IL-35 was increased in patients with an early SSc pattern on capillaroscopy assessment compared with those with active and late SSc patterns.The present study demonstrates overexpression of IL-35 in SSc skin, dermal fibroblasts and serum. TGF-? induces IL-35, which in turn activates resting fibroblasts and enhances the release of collagen, thereby contributing to aberrant TGF-? signalling in SSc. Increased serum IL-35 is associated with early, inflammatory stages of SSc.
EVALuna2:13159